Development of a Project-Based Learning-Oriented Practicum Guide on the Respiratory System to Enhance Junior High School Students’ Critical Thinking Skills - Genny Anggriani; Siti Darwa Suryani; Merri Sri Hartati (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study was motivated by the lack of science practicum guides on the respiratory system that are systematically integrated with Project-Based Learning (PjBL) to enhance junior high school students’ critical thinking skills. This study aims to develop and evaluate the validity, practicality, and effectiveness of a PjBL-based practicum guide. A Research and Development (R&D) approach using the ADDIE model was employed, combined with a comparative design involving experimental and control groups. The participants were eighth-grade students from two junior high schools in Central Bengkulu. Data were collected using expert validation sheets, student response questionnaires, and pretest–posttest instruments. The results indicate that the developed practicum guide achieved very high validity (media: 96%; material: 94%) and excellent practicality (97.45%). The effectiveness test showed that the experimental group outperformed the control group, with a significant difference (p < 0.001). These findings confirm that the PjBL-based practicum guide is effective in improving students’ critical thinking skills.